Developments in Platinum-Group Metals as Dual Antibacterial and Anticancer Agents. (6th November 2019) - Odularu, Ayodele T.; Ajibade, Peter A.; Mbese, Johannes Z.; Oyedeji, Opeoluwa O.
Abstract : Platinum-group (PG) complexes have been used as antibacterial and anticancer agents since the discovery of cisplatin. The science world still requires improvement on these complexes because of multidrug and antineoplastic resistances. This review observes discoverers and history of these platinum-group metals (PGMs), as well as their beneficial applications. The focus of this study was biological applications of PGMs in relation to human health. Sandwich and half-sandwich PGM coordination compounds and their metal nanoparticles give improved results for biological activities by enhancing efficient delivery of both antibacterial and anticancer drugs, as well as luminescent bioimaging (biomarkers) for biological identifications.